The development of preservice teachers topics specific pedagogical content knowledge using seleced components of the construct - Sekhibane, Thandiwe Lerato (My University, 2018)
This study was concerned with assisting pre service teachers who were in the beginning stages of their Bachelor of Education (B. Ed) programme. This development was focused on content knowledge (CK) on the topic of chemical bonding making use of the Topic Specific Pedagogical Content Knowledge model which enables transformation of science CK using five components. These are learner prior knowledge, representations, curricular saliency, what makes the topic easy or difficult to teach and conceptual teaching strategies. The students referred were a sample of 30 early pre service teachers (EPT) registered in the second year Natural Sciences Methodology II course. CK and TSPCK development was fostered through the use of three components during a 6-week intervention. I adopted a Mixed Methods research design (MM) and gathered both qualitative (written tasks and semi structured interviews) and quantitative (CK and TSPCK tests) data. The results in the study show: (1) that there was general improvement in CK in pre and post-tests (2) that there was evidence of general improvement in TSPCK components used in the intervention; (3) that there was evidence of general improvement across the three components; (4) that there was interaction of TSPCK components observed, including those in those components that were not covered in the course; (5) that pre service teachers were observed to be using their knowledge of the topic of chemical bonding to draw on similarities and differences between the concepts imbedded in the topic of intervention, (6) that pre service teachers at their beginning stages of teacher training display, in planning, that they ‘miss’ the important aspects of teaching chemical bonding and (7) pre service teachers in their beginning stages of their teacher education programme developed explicit ways of thinking about their teacher knowledge. It was recommended that further research is needed regarding the nature and development of the interaction among preservice teachers' PCK components, and regarding how various contexts can stimulate the development and strengthen the interaction of these components. Furthermore, it has been suggested that more focus should be on the four aspects highlighted as the core problems in the learning of chemical bonding. The four problems were (1) EPT’s showed no mention of the electrostatic nature of chemical bonding, (2) EPT’s used macroscopic levels of representations to explain and describe bonding (3) EPT’s in the study over emphasized the rule of the octet to explain chemical bonds (4) EPT’s struggle with the idea of delocalized electrons in metals and since EPTs have shown that ii they prefer the macroscopic representations, rather teacher educators focus on developing this preference to enhance their learning. Key words Topic specific pedagogical content knowledge, content knowledge, early pre service teachers, chemical bonding, transformation
A research report submitted to the faculty of Science, in partial fulflment of the requirements for the degree of Masters of Science by combination of coursework and research, University of the Witwatersrand, Johannesburg, 2018 Johannesburg, 2018
Keywords: Electric circuits--Study and teaching; Pedagogical content knowledge; Science teachers--South Africa